Enhancing Pond Productivity of Indian Butter Catfish (Ompok bimaculatus): Impact of Protein-Rich Feeds over Conventional Feed: Improving Ompok bimaculatus Aquaculture with High-Protein Feeds - Debnath, Chandan; Lopamudra Sahoo (Fishery Technology, 2024)
Ompok bimaculatus (Pabda fish), is a sought-after fish in Eastern and North-eastern India, and is cultivated extensively in these regions by feeding traditional feeds intended for carps, which may not meet always the high protein requirements of this fish. A study was carried for over six months in earthen ponds to evaluate the impact of different diets on the growth of with a stocking density of 4000 fish per hectare. Three types of feed were tested: a conventional feed with 23.84% crude protein (CP), and two protein-rich feeds with 30.47% and 35.24% CP, respectively. The feeding rate varied from 2% to 4% of the fish biomass. Water quality and plankton were monitored monthly. The fish on the higher protein diets showed significantly better growth rates and weight gain compared to those on the conventional diet. Survival rates increased by 15%15.2%, and total biomass improved by 126.3 to 132 kg/ha with the higher protein feeds. The feed conversion ratio was also better with high protein feeds. No significant differences in growth or survival were noted between the two higher protein feeds. The overall composition of the fish flesh determined by proximate analysis remained consistent across all diets. The study concludes that a minimum of 30% CP in feed is essential for the effective pond cultivation of Pabda fish, particularly in low-input systems.